ACTIVITY DIVERSITY AND WELL-BEING OF SENIOR LIVING RESIDENTS AND COMMUNITY-DWELLERS. (16th November 2018) - Basic, A; Bihary, J; Smith, J; O'Brien, C; Nicholson, R; O'Connor, D
Abstract: Previous research has found that higher activity diversity is associated with better psychological well-being for older adults. Opportunities to engage in a variety of activities, and the associated benefits to well-being, may be greater for older adults who live in service-rich environments, such as Life Plan Communities. Thus, the current study examined whether the association between activity diversity and well-being is different for residents of Life Plan Communities compared to community-dwelling older adults. The sample included 4, 056 Life Plan Community residents and 834 community-dwelling older adults (overall mean age = 83.33, 63% female, 96% White/Caucasian). Participants completed surveys that measured their involvement in 21 daily activities as well as their well-being (loneliness, mood, perceptions of aging, and pessimism). Multilevel analyses were conducted with activity diversity (i.e., number of different daily activities such as gardening, writing, cooking, etc.), type of residence, and the cross-product interaction term predicting well-being, controlling for age, gender, education, and health. Across all outcomes, analyses revealed that greater activity diversity was associated with better well-being, and residents reported better well-being compared to community-dwellers. In addition, there was a significant interaction between activity diversity and residence. The relationship between activity diversity and well-being was stronger for community-dwellers compared to residents, which suggested that community-dwelling older adults may have experienced more benefits from activity diversity. Aging services providers should support community-dwelling older adults in identifying diverse daily activities that they can engage in